The Relationship Between The Level Of Midwife Satisfaction With Improving The Quality Of MCH Services In The Working Area Of Muara Dua Health Center In Lhokseumawe City - Nizan Mauyah; Subki Subki; Syahabuddin Syahabuddin; Burdah Burdah (Jurnal EduHealth, 2023)
The background of this study is the complexity of factors that affect midwives' job satisfaction, especially at Muara Dua Health Center, Lhokseumawe. Job satisfaction is related to motivation, continuing education, salary and benefits, management, tasks, work environment, workload, and moral satisfaction. The characteristics of motivational factors are distinguished between intrinsic characteristics such as challenge, recognition, autonomy, work, and responsibility that determine job satisfaction. Extrinsic characteristics such as salary, security in work, working conditions. Job dissatisfaction can lead to delays and absences, inability to conduct proper checks, work fatigue. To determine the relationship between the level of midwife satisfaction with improving the quality of maternal and child health services at the Muara Dua Health Center in Lhokseumawe City. The study was conducted on 55 samples of midwives at the Blang Muara Dua Health Center, Muara Dua District, Lhokseumawe City, with a comfortable cross-sectional work design, giving satisfaction to 14 midwives (58.3%) and 10 uncomfortable people (41.7%). Meanwhile, 31 respondents were satisfied with a comfortable work environment by 19 people (61.3%) and dissatisfied with an uncomfortable work environment by 12 people (36.7%). Based on statistical tests on bivariate analysis with the Exact Fisher test at a 95% confidence level, a value of P = 0.084 (p < 0.05) was obtained, meaning that there was no significant relationship between a comfortable work environment and the level of midwife satisfaction. There is a significant relationship between the distribution of service fees in accordance with midwives' satisfaction in improving the performance of maternal and child health services. At the same time, there is no meaningful relationship between the comfort of the work environment and the level of midwives' satisfaction in improving the performance of maternal and child health services. There is a significant relationship between the distribution of tasks and midwife satisfaction in improving the performance of maternal and child health services. There is no significant relationship between leadership elements and midwives' satisfaction in improving the performance of maternal and child health services.